Answer:
Degree:3
Y-intercept:-6
Step-by-step explanation:
The given function is:
[tex]f(x) = - {(x + 1)}^{2}( {2x - 3)}(x +2 )[/tex]
To find the degree, we multiply out the leading terms of each factor.
The leading term of the first factor is:
[tex] - {x}^{2} [/tex]
and that of the second factor is
[tex]2x[/tex]
and the third one is:
[tex]x[/tex]
If we multiply out the leading terms, we would get:
[tex] - {x}^{2} \times 2x \times x = - 2 {x}^{3} [/tex]
Therefore the degree of the function is:
3
To find the y-intercept, we put x=0 to get:
[tex]f(0) = - {(0 + 1)}^{2}( {2 \times 0 - 3)}(0 +2 )[/tex]
[tex] \implies \: f(0) = ( 1)( - 3) \times (2) = - 6[/tex]